Relational approaches to sustainability transformations: walking together in a world of many worlds - Simon West; L. Jamila Haider; Tilman Hertz; Maria Mancilla Garcia; Michele-Lee Moore (Ecosystems and People)
Transformations to sustainability require alternatives to the paradigms, practices, and policies that have generated social-ecological destruction and the Anthropocene. In sustainability science, several conceptual frameworks have been developed for transformations, including social-ecological, multi-level, transformative adaptation, and pathways approaches. There is a growing shift towards recognising transformations as ‘shared spaces’ involving multiple ways of knowing, being, and doing. Diverse relational approaches to transformations are increasingly articulated by Indigenous, humanities, and social science scholars, practitioners, and activists from the Global South and North. Broadly, relational approaches enact alternatives to separable categories of society and nature, emphasise unfolding relations between human and non-human beings, and highlight the importance of ethical responsibilities and care for these relationships. Yet while it is important to recognise the collective significance of diverse relational lifeways, practices, and philosophies to transformations, it is also vital to recognise their differences: efforts to produce universal frameworks and toolboxes for applying relationality can reproduce modernist-colonialist knowledge practices, hinder recognition of the significance of relational approaches, and marginalise more radical approaches. In this paper we explore five intersecting ‘relationalities’ currently contributing to discussions around transformations: (i) Indigenous-kinship, (ii) systemic-analytical, (iii) posthumanist-performative, (iv) structural-metabolic, and (v) Latin American-postdevelopment. We explore how these different relational approaches address key concepts in transformations research, including human-nature connectedness; agency and leadership; scale and scaling; time and change; and knowledge and action. We suggest that their diversity gives rise to practices of transformations as ‘walking together in a world of many worlds’ and support intercultural dialogue on sustainability transformations.